2015
DOI: 10.1371/journal.pone.0135479
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Neural Progenitor-Like Cells from Human Fibroblasts via a Genetic Material-Free Approach

Abstract: BackgroundA number of studies generated induced neural progenitor cells (iNPCs) from human fibroblasts by viral delivering defined transcription factors. However, the potential risks associated with gene delivery systems have limited their clinical use. We propose it would be safer to induce neural progenitor-like cells from human adult fibroblasts via a direct non-genetic alternative approach.Methodology/Principal FindingsHere, we have reported that seven rounds of TAT-SOX2 protein transduction in a defined c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Two studies reported that lentivirus-mediated expression of OCT4 is sufficient to obtain iNSCs from adult human fibroblasts, neonatal cord, and peripheral blood cells [29,30]. Besides Oct4, also Sox2 has been reported to be sufficient for direct conversion of somatic cells into iNSCs [32][33][34]. Dual SMAD inhibition is known to efficiently and rapidly convert pluripotent cells into neural cells [31], potentially indicating that reprogrammed cells might have passed a transient pluripotent stage.…”
Section: Transcription Factors Employed In Insc Generationmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies reported that lentivirus-mediated expression of OCT4 is sufficient to obtain iNSCs from adult human fibroblasts, neonatal cord, and peripheral blood cells [29,30]. Besides Oct4, also Sox2 has been reported to be sufficient for direct conversion of somatic cells into iNSCs [32][33][34]. Dual SMAD inhibition is known to efficiently and rapidly convert pluripotent cells into neural cells [31], potentially indicating that reprogrammed cells might have passed a transient pluripotent stage.…”
Section: Transcription Factors Employed In Insc Generationmentioning
confidence: 99%
“…A key question to assess the outcome of direct conversion strategies is to which extent directly converted iNSCs recapitulate these characteristics [11,71]. In order to demonstrate selfrenewal potential and clonal growth ability, iNSCs were either cultivated as primary and secondary neurospheres [33,34], analyzed in colony formation assays [28,33,36,39,42,48,72], and/or passaged several times [11,13,14,26,30,32,33,38,57,59,60,73]. On the other hand, all iNSC populations have been reported to express pan-neural markers, to be at least bipotential, and to show self-renewal and clonal growth ( Table 2).…”
Section: Molecular and Cellular Characterization Of Inscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, the result showed a quite low transduction efficiency, but a high viability (~100%) after transfection. Similarly, 3D sphere induced neural progenitor like cells from fibroblast were reported [106, 107]. Although the repeated transduction is necessary due to the low transduction efficiency, it can be free form the potential risk of viral vector such as gene disruption, instability, and tumor formation [108].…”
Section: Introductionmentioning
confidence: 99%